Study of the electron-phonon coupling in PbS/MnTe quantum dots based on temperature-dependent photoluminescence - Halim, Nur Diyana; Zaini, Muhammad Safwan; Talib, Zainal Abidin; Liew, Josephine Ying Chyi; Ahmad Kamarudin, Mazliana (Multidisciplinary Digital Publishing Institute, 2022)
The temperature dependence of photoluminescence (PL) emission is a valuable tool for investigating carrier localization, recombination, and carrier–phonon interactions. Herein, electron–phonon couplings in lead sulfide (PbS) quantum dots (QDs) and lead sulfide/manganese tellurite (PbS/MnTe) QDs is reported. The effect of temperature on the PL emission of PbS and PbS/MnTe was explored within a temperature range of 10 to 300 K. When temperature increased, PL emission was blue-shifted due to the confinement effect. The gradual broadening of the full width at half maximum (FWHM) with increasing temperature indicates electron–phonon interactions. An analysis based on the Boson model revealed that the values of the exciton acoustic phonon coupling coefficient, σ, and temperature-dependent linewidth, γ, for PbS/MnTe were larger than those for PbS, indicating stronger exciton longitudinal-optical–phonon coupling in the compound structure.